Measurements of sub-nT dynamic magnetic field shielding with soft iron and mu-metal for use in linear colliders - Gohil, C; Burrows, PN; Kraljevic, NB; Schulte, D; Heilig, B (IOP Publishing, 2020)
There is an increasing need to shield beams and accelerator elements from stray magnetic fields. The application of magnetic shielding in linear colliders is discussed. The shielding performance of soft iron and mu-metal is measured for magnetic fields of varying amplitude and frequency. Special attention is given to characterise the shielding performance for very small-amplitude magnetic fields.